Under Wildwood - Meloy, Colin (Meloy, Colin. Wildwood chronicles ;, 2012)
Prue McKeel has returned from the Impassable Wilderness after saving her brother from the evil Dowager Governess. Now her old life of school seems so boring in comparison, and she frequently gets bad grades. Luckily, or unluckily, a new threat is coming against the Wildwood, in which dark assassins have begun to settle old scores, and an industrial tyrant has begun using orphans to exploit the Impassable Wilderness. Prue is called back, and together with her bandit-in-training friend Curtis she will have to save the world, once again.